Modulating the photocatalytic redox preferences between anatase TiO2 001 and 101 surfaces. Issue 4 (21st December 2016) - Zhou, Peng; Zhang, Hongna; Ji, Hongwei; Ma, Wanhong; Chen, Chuncheng; Zhao, Jincai
Abstract : The surface protonation/deprotonation can change the photocatalytic redox preferences of TiO2 001 and 101 surfaces. Abstract : It is widely believed that anatase TiO2 001 and 101 surfaces acts as the oxidative and reductive sites in photocatalytic reactions, respectively, which is attributed to their different intrinsic surface structures. However, we demonstrate that the photocatalytic redox preferences of TiO2 001 and 101 surfaces are determined by the adsorbate-reconstructed surface structure instead of their intrinsic surface structures, which can be modulated by surface protonation/deprotonation.